Diversity and growth-effects of ectomycorrhizal fungi of a Nothofagus pumilio forest in the Andes of Southern Chile - Marín, César; Valenzuela, Eduardo; Godoy, Roberto; Palfner, Götz (Boletín Micológico, 2018)
Chilean temperate rainforests have unique climatic, edaphic and biotic conditions, constituting pre-industrial blueprint ecosystems. Mycorrhizal associations play a central role in the biogeochemical processes of these ecosystems´ functioning. Baseline forest ecology studies are necessary in order to better understand diversity patterns, specifically regarding mycorrhizal symbiosis. Therefore, here we described the vegetation characteristics and the mycorrhizal relationships of vascular plants in a Nothofagus pumilio forest. We also described, via morphological methods, the ectomycorrhizal diversity present in this forest. Additionally, we determined whether ectomycorrhizal inoculations confer positive growth effects on N. pumilio seedlings. We founded that from 46 described vascular plant species, 42 (91%) were associated with mycorrhizae and of these 33 (72%) were associated with arbuscular mycorrhizae (AM), two (the dominant trees N. pumilio and N. dombeyi) were associated with ectomycorrhizae (EM), five were associated with ericoid mycorrhizae, two with orchid mycorrhizae, and four were non-mycorrhizal. Additionally, 26 EM species were detected of which 14 belong to Cortinarius. Finally, there were clear differences in the growth of N. pumilio seedlings inoculated with the ectomycorrhizal fungus Laccaria laccata compared to non-inoculated plants. We suggest that mycorrhizal fungi play a key role in seedling colonization of extreme environments such as the Andean treeline.